Joint Noise Reduction for Contrast Enhancement in Stokes Polarimetric Imaging - Hui Wang; Haofeng Hu; Xiaobo Li; Lin Zhao; Zijian Guan; Wanshan Zhu; Junfeng Jiang; Kun Liu; Zhenzhou Cheng; Tiegen Liu (IEEE Photonics Journal)
Contrast optimization is a key issue in polarimetric imaging for the purpose of target detection. In practice, the noise could induce the intensity fluctuation of the image and thus lead to the decrease of the image contrast. A joint noise reduction method is proposed for contrast enhancement in Stokes polarimetric imaging. The proposed method is based on the relation of the joint polarimetric image set, which includes four images taken to calculate Stokes vector and one image taken at the optimal state of a polarization state analyzer (PSA). By our method, the traditional contrast-enhanced image is modified to decrease the disturbance of noise, and the contrast of the image is further enhanced. Both the theoretical analysis and the real-world experimental results demonstrate that our method can effectively decrease the disturbance by the noise and thus increase the contrast of the image. In particular, it is found that the effect of the proposed method is independent of the optimal PSA state when the regular tetrahedron measurement matrix is implemented.